Characterizing the dynamic frequency structure of fast oscillations in the rodent hippocampus - Nguyen, David P.; Kloosterman, Fabian; Barbieri, Riccardo; Brown, Emery N.; Wilson, Matthew A. (Frontiers in Integrative Neuroscience, 2009)
Fast oscillations or “ripples” are found in the local field potential (LFP) of the rodent hippocampus during awake and sleep states. Ripples have been found to correlate with memory related neural processing, however, the functional role of the ripple has yet to be fully established. We applied a Kalman smoother based estimator of instantaneous frequency (iFreq) and frequency modulation (FM) to ripple oscillations recorded in-vivo from region CA1 of the rat and mouse hippocampus during slow wave sleep. We found that 1) ripples exhibit stereotypical frequency dynamics that are consistent in the rat and mouse, 2) instantaneous frequency information may be used as an additional dimension in the classification of ripple events, and 3) the instantaneous frequency structure of ripples may be used to improve the detection of ripple events by reducing Type I and Type II errors. Based on our results, we propose that high temporal and spectral resolution estimates of frequency dynamics may be used to help elucidate the mechanisms of ripple generation and memory related processing.